A high-efficiency freeform reflector for a light-emitting diode low-beam headlamp. (December 2016) - Wu, H; Zhang, XM; Ge, P; Yu, JD
A practical method is proposed for the design of a freeform reflector for light-emitting diode low-beam headlamps. The energy relationship between the solid angle of the light-emitting diode source and the target plane is first established. A freeform reflector is then constructed based on Snell's Law and the light energy redistribution maps are obtained by optimising meshing parameters on the target plane. By using this method, four reflectors are designed to constitute a module for the low-beam headlamp, and three different types of light-emitting diode sources are selected for simulation. Results demonstrate that the best light pattern can be obtained with the LUW HWQP light-emitting diode source whose chip size is 1.0 mm×1.0 mm, and the lighting distribution can fully satisfy the requirements of the ECE R112 regulations without any other lenses, shields or baffles. Furthermore, the optical efficiency can reach up to 79%.